Immediate Effects of tDCS on the μ-Opioid System of a Chronic Pain Patient - DosSantos, Marcos F.; Love, Tiffany M.; Martikainen, Ilkka K.; Nascimento, Thiago D.; Fregni, Felipe; Cummiford, Chelsea; Deboer, Misty D.; Zubieta, Jon K.; DaSilva, Alexandre F. (Frontiers in Psychiatry, 2012)
We developed a unique protocol where transcranial direct current stimulation (tDCS) of the motor cortex is performed during positron emission tomography (PET) scan using a µ-opioid receptor (µOR) selective radiotracer, [11C]carfentanil. This is one of the most important central neuromechanisms associated with pain perception and regulation. We measured µOR non-displaceable binding potential (µOR BPND) in a trigeminal neuropathic pain patient (TNP) without creating artifacts, or posing risks to the patient (e.g., monitoring of resistance). The active session directly improved in 36.2% the threshold for experimental cold pain in the trigeminal allodynic area, mandibular branch, but not the TNP patient’s clinical pain. Interestingly, the single active tDCS application considerably decreased µORBPND levels in (sub)cortical pain-matrix structures compared to sham tDCS, especially in the posterior thalamus. Suggesting that the µ-opioidergic effects of a single tDCS session are subclinical at immediate level, and repetitive sessions are necessary to revert ingrained neuroplastic changes related to the chronic pain. To our knowledge, we provide data for the first time in-vivo that there is possibly an instant increase of endogenous µ-opioid release during acute motor cortex neuromodulation with tDCS.